Identiﬁcation and molecular mapping of a gene YrFL in wheat cultivar Flanders with durable resistance to stripe rust - Wu, Caijuan; Ma, Kangjie; Chen, Wenbin; Li, Jianhao; Liu, Mingjie; Cheng, Peng; Wang, Baotong; Li, Qiang (Plant disease, 2023)
Stripe rust, caused by Puccinia striiformis f. sp. tritici (Pst), is one of the most severe diseases of wheat (Triticum aestivum L.) worldwide. Identification and characterization of resistance genes is advantageous to cultivating wheat varieties with durable resistance, which is the most economic and effective strategy to control stripe rust. Flanders, a common wheat variety released in France in 1986, confers effective resistance to stripe rust both at seedling and adult plant stages. To elucidate the genetic basis of resistance in Flanders, F1, F2 and F2:3 generations derived from the cross Mingxian169×Flanders were evaluated with the most prevalent Chinese Pst race CYR33 at seedling stage. Inheritance analysis showed that the stripe rust resistance of Flanders was controlled by a single dominant gene, temporarily designated as YrFL. Bulked segregant analysis (BSA) combined with wheat 660K single-nucleotide polymorphism (SNP) array indicated that polymorphic SNP markers were mainly located in the 0-150 Mb on wheat chromosome 5A. One hundred and eleven kompetitive allele-specific PCR (KASP) and 39 simple sequence repeat (SSR) markers on chromosome 5A were used to locate the YrFL. Linkage analysis mapped YrFL with 19 KASP and 3 SSR markers on wheat chromosome 5AS, and the genetic distances of the closest flanking markers AX108925494 and Xbarc56 to YrFL were 0.6 cM and 2.0 cM, respectively. Chromosome location, resistance characterization, and molecular marker positions indicated that YrFL is likely a novel stripe rust resistance gene on wheat chromosome 5AS, and could be pyramided with other resistance genes to improve resistance in wheat breeding programs.